Effect of azo dye on ammonium oxidation process and ammonia-oxidizing bacteria (AOB) in soil. Issue 44 (16th May 2015) - Batool, Samavia; Khalid, Azeem; Jalal, Khan Chowdhury Ahmed; Sarfraz, Maliha; Balkhair, Khaled S.; Ashraf, Muhammad Aqeel
<x xml:space="preserve">Abstract</x> Ammonia-oxidizing bacteria (AOB) play a key role in the production of nitrate-N (NO3−-N) in terrestrial ecosystems.